Common prescription errors among dentists in the middle east: A comprehensive literature review - Hala Afifi; Sarah Dheaa; Albanna, Farah; Farah Alqaderi (Journal of University Medical & Dental College, 2025)
BACKGROUND AND OBJECTIVE: Prescription errors in healthcare pose significant risks, leading to adverse patient outcomes and escalating healthcare costs. In dentistry, mistakes like incorrect drug choice or dosage can cause serious complications. Although these risks are well-known, limited research focuses specifically on dental prescription errors in the Middle East. This study aims to investigate common prescription errors within this region’s dental field and identify factors that could help improve patient safety and elevate care standards. METHODOLOGY: A literature review of existing studies was performed utilizing databases such as Google Scholar, Scopus, and PubMed, zeroing in on dental prescription errors related to the Middle East. RESULTS: The data reveals common errors include wrong drug choice, prescribing unsafe drugs, inappropriate treatment length, incomplete patient information, wrong dosage, and poor communication with patients. CONCLUSION: As highlighted in the study, immediate targeted measures are required to create safer dental prescribing in the Middle East. Recommendations encompass providing ongoing training, performing regular audits, and using electronic prescribing systems. Teamwork between healthcare providers is crucial to creating hypervigilance of prescribing in dental care and improving medication safety.